Patient-subject constructions in Mandarin Chinese syntax, semantics, discourse - He, Xiaoling (Studies in Chinese language and discourse (SCLD) ;, 2019)
"As a distinctive syntactic structure in Mandarin Chinese, the Patient-Subject Construction (PSC) is one of the most interesting but least well-understood structures in the language. This book offers a comprehensive account of the history, structure, meaning and use of the PSC. Unlike previous descriptions which were framed in terms of pre-existing grammatical notions such as 'topicalization', 'passivization' and 'ergativization', this book offers a fresh look at the PSC, in which its syntactic and semantic as well as its discourse functions are examined within the system of major construction-types of the language as a whole. The PSC, being low in transitivity, serves primarily the function of backgrounding in discourse. Typologically, the PSC bears a resemblance to middle constructions in Indo-European and other languages, raising interesting questions about ways to understand congruent and divergent syntactic structures across the world's languages. This book will be of interest to students of Chinese Linguistics as well as Language Typology"--